Agromyzidae of Greece (Bollettino di zoologia agraria e bachicoltura, 2024)
14 species of Agromyzidae have been collected in the years 1999-2003 new for Greece. Other 27 species are known in the past years and from different Authors examined, as contribution to the knowledge of the fauna of this leaf-miners of the Greece.
Keywords: Agromyzidae; leaf miners; Greece; new records